Perceived risk, anxiety and international travel decisions in post-pandemic context: The case of Bali - Babolian Hendijani, Roozbeh; Jaszus, Kathrin (Turyzm/Tourism, 2026)
Understanding international tourists’ decision-making during periods of uncertainty is crucial for tourism recovery and destination management. Despite the significant disruption of global travel caused by COVID-19, limited empirical research has examined how tourists’ risk perception and anxiety influence international travel decisions following border reopening. Therefore, this study investigates the factors influencing such decision-making by integrating risk perception and anxiety into the theory of planned behavior (TPB). This study has developed a theoretical framework that combines risk perception, anxiety and TPB. A quantitative approach was used to measure inbound tourists’ decision-making for their trip to Bali after COVID-19. Self-administered surveys consisting of ten sections (physical, psychological, financial and time risks, anxiety, attitude, subjective norms, perceived behavioral control, travel decisions and socio-demographic factors) were distributed to respondents. A total of 487 valid responses were analyzed using partial least squares structural equation modeling. Findings show that perceived behavioral control, subjective norms and attitudes significantly influence international tourists’ travel decisions. Perceived behavioral control showing the strongest predictive value. While perceived psychological or physical risks did not directly affect travel decisions, all risk dimensions significantly increased travel-related anxiety. Implications for destination management organizations and marketing professionals in the post-pandemic era are discussed.